Thursday

December 18, 2014

December 18, 2014

Posted by **Jasmine202005** on Sunday, October 22, 2006 at 8:55pm.

x+y=1

y-z=-3

2x+3y+z=1

THE ANSWERS ARE3,-2,1 HOW DID THEY GET THAT ANSWER.

This can be solved a number of ways.

1) subsitition

2) determinants

3) matricies.

Substution:

x= 1-y

y= z+3 or x= 1-z-3

In the third equation , put those two things for x, and y.

2x+3y+z=1

then solve for z. Then go back and solve for x and y.

I've done that already such as

the book states the following

that the answer is -x-y=-1

how did they get there after adding equation 2 and three

Substitute x = 1-y and z = y+3 in the third equation. Then you get an equation in y only:

2(1-y) + 3y + (y+3) = 1

2y + 5 = 1

y = -2

Then use the equations for x and z again.

x = 1-(-2) = 3 etc.

**Answer this Question**

**Related Questions**

to annonymus can you help me with math - How do i solve inequalitites with three...

TO DRWLS/MATH HELP PLEASE - How do i solve inequalitites with three variables. I...

math - How do i solve inequalitites with three variables. I still can't figure ...

Math Help Please - How do i solve inequalitites with three variables. I still ...

a.p. calculus help please! - My a.p. calculus teacher doesn't know how to do ...

Algebra - I was given this problem to solve and no matter what order I multiply ...

Precalculus - I asked this yesterday but I was told my answer was incorrect by ...

Physics - Two 0.09g pith balls are suspended from the same point by threads 40cm...

math - In the space below, indicate the values stored in the variables A,B,C, ...

Math Riddle - In a little town in West Michigan lives a math professor, who ...